Dominasi Teknologi di Era AI dan Pergeseran Otoritas Guru dalam Pendidikan - Syifa Fajriyah; Muhammad Irfan; Rufaidah; Abdul Fadhil (Advances In Education Journal, 2026)
Artificial Intelligence (AI) has significantly transformed the educational landscape by changing how teachers deliver instruction and how students access knowledge. The emergence of Generative AI tools, such as ChatGPT, Gemini, Claude, and Microsoft Copilot, has reduced students' dependence on teachers as the primary source of information while creating new opportunities for personalized and technology-assisted learning. This study aims to examine the shift in teacher authority in the AI era, identify its impacts on teachers and students, and explore strategies for integrating AI into education without diminishing the essential role of teachers. A qualitative descriptive approach with a literature review method was employed by analyzing recent national and international scholarly publications related to AI, teacher authority, and educational transformation. The findings indicate that AI enhances learning efficiency, supports personalized instruction, and improves access to educational resources. However, it also challenges teachers' traditional authority and requires stronger digital literacy and ethical guidance. Therefore, AI should function as a complementary.